Disinfectant potential in inactivation of epidemic keratoconjunctivitis-related adenoviruses by potassium peroxymonosulfate. Issue 2 (March 2021) - Hashizume, Mei; Aoki, Koki; Ohno, Shigeaki; Kitaichi, Nobuyoshi; Yawata, Nobuyo; Gonzalez, Gabriel; Nonaka, Hirotaka; Sato, Seiichi; Takaoka, Akinori
Purpose: The aim of this study was to test the antiviral effectivity of potassium peroxymonosulfate (RUBYSTA ®, KYORIN) against five epidemic keratoconjunctivitis-related types of Human adenovirus D in vitro. Methods: Five types of Human adenovirus D (8, 37, 53, 54 and 56) were incubated with 1% potassium peroxymonosulfate, 0.1% sodium hypochlorite (NaClO) or alcohol-based disinfectant for 30 s or 1 min. These solutions were subjected to measurements of viral titres by infection assays in A549 cells. At day 6 post-infection, both, supernatants and cells, were collected and the viral genome was assessed by real-time polymerase chain reaction analysis. Results: Treatments with 1% potassium peroxymonosulfate led to significant reduction in all tested Human adenovirus D types comparable to disinfecting effects by 0.1% NaClO. Overall, potassium peroxymonosulfate demonstrated sufficient inactivation of the major epidemic keratoconjunctivitis-causing Human adenovirus D to be considered for disinfection and prevention purposes in ophthalmological clinics and hospitals. Conclusion: This study demonstrated that potassium peroxymonosulfate is a promising disinfectant for the prevention of epidemic keratoconjunctivitis nosocomial infections in ophthalmological clinics.